The identity of Homalium breviracemosum (Salicaceae) - Xu, Shenjian; Shang, Ce; Zhang, Zhixiang; Zhao, Liangcheng (Phytotaxa, 2017)
The taxonomic status of Homalium breviracemosum How & Ko (Salicaceae), a species endemic to China, has long been questionable. Due to lack of material, the reliability of its taxonomic characters is unknown and the species has been retained. Following extensive field investigations, population sampling and examination of specimens, we consider that the characters previously used to distinguish between H. breviracemosum and H. cochinchinense (Loureiro) Druce, i.e. the length of inflorescences and the density of indumentum, vary continuously within populations and should not be used to distinguish between the two species. Therefore, the name H. breviracemosum is here reduced to the synonym of H. cochinchinense.